Effect of different composite core materials on fracture resistance of endodontically treated teeth restored with FRC posts - Prapaporn PANITIWAT; Prarom SALIMEE
Abstract Objective This study evaluated the fracture resistance of endodontically treated teeth restored with fiber reinforced composite posts, using three resin composite core build-up materials, (Clearfil Photo Core (CPC), MultiCore Flow (MCF), and LuxaCore Z-Dual (LCZ)), and a nanohybrid composite, (Tetric N-Ceram (TNC)). Material and Methods Forty endodontically treated lower first premolars were restored with quartz fiber posts (D.T. Light-Post) cemented with resin cement (Panavia F2.0). Samples were randomly divided into four groups (n=10). Each group was built-up with one of the four core materials following its manufacturers' instructions. The teeth were embedded in acrylic resin blocks. Nickel-Chromium crowns were fixed on the specimens with resin cement. The fracture resistance was determined using a universal testing machine with a crosshead speed of 1 mm/min at 1350 to the tooth axis until failure occurred. All core materials used in the study were subjected to test for the flexural modulus according to ISO 4049:2009. Results One-way ANOVA and Bonferroni multiple comparisons test indicated that the fracture resistance was higher in the groups with CPC and MCF, which presented no statistically significant difference (p>0.05), but was significantly higher than in those with LCZ and TNC (p<0.05). In terms of the flexural modulus, the ranking from the highest values of the materials was aligned with the same tendency of fracture loads. Conclusion Among the cores used in this study, the composite core with high filler content tended to enhance fracture thresholds of teeth restored with fiber posts more than others.